Comparison of Total Intravenous with Inhalational Anesthesia in Term of Post-Operative Delirium and Complication in Older Patients (The Insight, 2024)
Introduction: Postoperative delirium is a common complication of major surgery, occurring in up to 50% of older patients. It is associated with poorer surgical outcomes including higher morbidity and mortality. The choice of anaesthetic technique has been proposed as a modifiable risk factor. Objective: This study compared the evidence for total intravenous anaesthesia (TIVA) versus inhalational anaesthesia with regard to postoperative delirium and other complications.  Methods and materials: The study was carried out under Analgesia & Intensive Care Medicine, Jalalabad Ragib-rabeya Medical College Hospital, Sylhet, Bangladesh between July and December 2023. The patients were scheduled to undergo elective gastrectomy, colectomy, or rectectomy under general anaesthesia combined with epidural anaesthesia. Patients in Group A received inhalation anaesthesia, and those in Group B received TIVA. Results:  Eight patients in group A and 2 in group B developed POD. The incidence of POD in group B (6.9%) was significantly less than that in group A (26.7%; P = .038). Twenty male and 10 female patients were included in group A, and 11 male and 9 female patients were included in group B. In group A, 7 of the 8 patients who developed POD were male, and in group B, both of the patients who developed POD were male. Conclusion: Based on the current evidence, TIVA appears superior to inhalational agents for reducing postoperative delirium. However, study quality and size vary, and more research is still warranted.
Keywords: Total intravenous anaesthesia; inhalational anaesthesia; post-operative delirium; older patients